A systematic review on academicians' job stress risk factors in public higher education institutions in the Asia Region - Syazwina Muhammad Khir,; Norashikin Mahmud,; Nurul Hidayah Mohamad Farok, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In recent years, academicians reported rising mental health issues, including stress pandemic, compared to other professions. Reports from past studies suggest many predictors of stress among academicians across the continents, especially in public universities. Nevertheless, there are still inadequate studies that are being systematically reviewed related to this topic in Asia. Hence, this paper aims to review the risk factors of stress from past literature systematically. In doing so, the reviewers utilised the bibliographic databases and search engines such as Scopus, Web of Sciences, Science Direct, and Emerald to search and extract records systematically. A total of eleven articles were included for the review after the process of quality assessment. The risk factors related to job stress are divided into two, which are individual factors and job factors. We found that job risk factors to be more critical than individual risk factors among academicians in public higher education institutions. Finally, individual and organisational level stress management interventions are suggested to reduce stress.